2021
DOI: 10.7717/peerj-cs.354
|View full text |Cite
|
Sign up to set email alerts
|

Age of information of a server with energy requirements

Abstract: We investigate a system with Poisson arrivals to two queues. One queue stores the status updates of the process of interest (or data packets) and the other handles the energy that is required to deliver the updates to the monitor. We consider that the energy is represented by packets of discrete unit. When an update ends service, it is sent to the energy queue and, if the energy queue has one packet, the update is delivered successfully and the energy packet disappears; however, in case the energy queue is emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…From these illustrations, we also conclude that the average Age of Information is not monotone with respect to α (note that in [19] it has been shown that the average Age of Information of a system with a single server with energy harvesting is monotone with respect to α). For instance, we see that, when p = 0.45 and λ = 10, the average Age of Information increases when λ is small, then decreases and finally decreases again.…”
Section: Convergence Analysis Of Propositionmentioning
confidence: 70%
See 2 more Smart Citations
“…From these illustrations, we also conclude that the average Age of Information is not monotone with respect to α (note that in [19] it has been shown that the average Age of Information of a system with a single server with energy harvesting is monotone with respect to α). For instance, we see that, when p = 0.45 and λ = 10, the average Age of Information increases when λ is small, then decreases and finally decreases again.…”
Section: Convergence Analysis Of Propositionmentioning
confidence: 70%
“…• the work of [19] where it is analyzed a system with a single server and energy harvesting. In our work, we consider the same energy harvesting model, but with two parallel servers.…”
Section: Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of works focusing on analyzing AoI when transmitters rely on energy harvesting to communicate, e.g., [3]- [40]. In summary, these works may be categorized according to the following three differentiating aspects:…”
Section: A Related Workmentioning
confidence: 99%
“…Thus, the WSN faces numerous problems concerning energy distribution ( Razzaque & Dobson, 2014 ). The utilization of power according to the amount of consumption among several components limits the lifetime of the energy sources Doncel, 2021 . Thus, it is essential to preserve the energy to maintain a balance in terms of power distribution.…”
Section: Introductionmentioning
confidence: 99%